PEMIKIRAN KEPEMIMPINAN BUYA HAMKA DALAM PERSPEKTIF KEPEMIMPINAN SITUASIONAL MODERN DAN IMPLIKASINYA TERHADAP KESIAPAN AKADEMIK SISWA SEKOLAH DASAR - Awaluddin, Andi; Wikastri, Ety Dwi; Rismita, Rismita (STKIP Pesisir Selatan, 2026)
This study aims to analyze Buya Hamka’s educational leadership thought within the framework of modern situational leadership and its relevance in optimizing students’ readiness at SD Negeri Kereo 3 in facing the Academic Ability Test (Tes Kemampuan Akademik/TKA). The issue addressed in this study arises from the challenge of elementary schools in preparing students not only cognitively but also psychologically and motivationally for standardized academic assessments, which requires adaptive, humanistic, and context-sensitive school leadership. This research employed a qualitative approach using a case study design. The findings reveal three main themes: leadership based on moral exemplarity and empathy, the application of situational leadership in academic guidance, and the holistic strengthening of students’ academic readiness. The integration of Buya Hamka’s leadership values with modern situational leadership principles contributes to the creation of a supportive academic climate and enhances students’ readiness to face TKA. This study provides a theoretical contribution to the development of value-based educational leadership grounded in local wisdom and offers practical implications for strengthening leadership practices in elementary schools to support students’ academic readiness.